Ni ALLOY HAVING EXCELLENT SURFACE PROPERTIES AND MECHANICAL PROPERTIES

JP2025031237AActive Publication Date: 2025-03-07NIPPON YAKIN IND KK
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023137323
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-03-07
Estimated Expiration
2043-08-25

AI Technical Summary

Benefits of technology

【0014】 その結果、欠陥発生は非金属介在物の組織形態と強く関連していて、CaO-Al2O3-MgO系の酸化物がMgOあるいはMgO·Al2O3を包含する組織形態は、クラスター化を抑止する能力が高い事を見出した。その模式図を図1に示す。図1(a)は、CaO-Al2O3-MgO系酸化物がその略球面内にMgOあるいはMgO·Al2O3を完全に包含しており、クラスター化を抑制できた良い形態である。一方で図1(b)のように、外縁部の一部がCaO-Al2O3-MgO系であり、内部の大半が高融点のMgOあるいはMgO·Al2O3酸化物であって介在物の略球面内から突出する形態であると、クラスター化を促進することが明らかとなった。その機構は不明な点が多いが、CaO-Al2O3-MgO系融体が、所謂、製鋼温度(1400~1550℃)にて焼結助剤の役割を担い、お互いに付着しては焼結するためと推定される。主たる焼結場所は、実機においては連続鋳造機の浸漬ノズル内壁と、経験上から憶測された。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031237000001_ABST
    Figure 2025031237000001_ABST
Patent Text Reader

Abstract

To provide a Ni-based alloy having sound surface properties and mechanical properties without surface defects by comprehensively considering the control of the composition and structural formation of non-metallic inclusions, and a method for producing the same.SOLUTION: There is provided a Ni alloy which comprises, by mass%, 0.001 to 0.03% of C, 0.01 to 0.5% of Si, 0.01 to 0.5% of Mn, 0.01% or less of P, 0.005% or less of S, 0.5% or less of Cr, 0.1% or less of Mo, 0.1% or less of Cu, 0.001 to 0.2% of Al, 0.05% or less of Ti, 0.01 to 0.5% of Fe, 0.0001 to 0.02% of Ca. 0.0001 to 0.02% of Mg, 0.005% or less of N, 0.005% or less of O, 1% or less of one or two or more of Co, W, Nb and B, the balance Ni, and inevitable impurities, wherein the average composition of non-metallic inclusions is 30 to 70% of MgO, 15 to 40% of Al2O3, 30% or less of SiO2, 10 to 40% of CaO, and 1% or less of MnO.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a Ni alloy having excellent surface properties and mechanical properties, and a method for producing the same. [Background technology]

[0002] Because pure nickel plate has excellent corrosion resistance, it is used in conductive components of internal wiring of rechargeable lithium ion batteries, lithium polymer batteries, nickel metal hydride batteries, and the like, which are power sources for portable electronic devices and the like (see, for example, Patent Documents 1 and 2).

[0003] Nickel plates become softer more easily than materials such as iron, and technology has been developed to maintain their strength (see, for example, Patent Document 3).

[0004] In addition, nickel rolled sheets for deep drawing are used in a wide range of applications, such as for electrodes in cold cathode fluorescent lamps.Similarly, because of its excellent corrosion resistance, especially in alkaline atmospheres, it is also used in nickel electrodes for caustic soda production (see, for example, Patent Documents 4 and 5).

[0005] As described above, because they are used in extremely precise locations, the occurrence of surface defects must be restricted. Also, since corrosion progresses from the defective parts, a technology to prevent this has been demanded (for example, see Patent Document 6).

[0006] Since such electronic components require soldering, efforts have been made to improve the wettability of the nickel plate with solder (see, for example, Patent Documents 7 and 8).

[0007] Furthermore, since nickel plate is expensive compared to commonly used metals such as iron and aluminum, not only is an increase in cost due to the occurrence of surface defects unacceptable, but hot workability must also be maintained at a high level (see, for example, Patent Documents 9-10).

[0008] In this context, nickel alloys with excellent surface properties have been disclosed. However, the structure of the nonmetallic inclusions is not controlled, and in some cases, surface defects are formed. Furthermore, it is sometimes difficult to maintain mechanical properties (see, for example, Patent Document 11). [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Application Publication No. 63-168259 [Patent Document 2] JP 2014-43623 A [Patent Document 3] JP 2010-90438 A [Patent Document 4] JP 2011-74437 A [Patent Document 5] JP 2003-89835 A [Patent Document 6] WO2010 / 064642 publication [Patent Document 7] JP 2005-82886 A [Patent Document 8] JP 2010-132933 A [Patent Document 9] Japanese Patent Application Publication No. 8-143996 [Patent Document 10] JP 2010-132934 A [Patent Document 11] Patent No. 7015410 Summary of the Invention [Problem to be solved by the invention]

[0010] As described above, the main aim of the present invention is to prevent clustering of nonmetallic inclusions, which can cause large surface defects, by controlling not only the composition of the nonmetallic inclusions but also their structure. Furthermore, the steel must have good mechanical properties. At the same time, the formation of CaO inclusions and Al2O3 inclusions must be prevented because they tend to cluster. Furthermore, MnO-Cr2O3-based inclusions are formed in an environment with a high oxygen concentration, so the total number of inclusions is large and they are also prone to clustering, so they must be prevented.

[0011] That is, an object of the present invention is to comprehensively consider the above and to provide a Ni alloy having sound surface properties and mechanical properties free from surface defects, and a method for producing the same. [Means for solving the problem]

[0012] In order to solve the problems of the above-mentioned conventional techniques, the inventors have repeatedly carried out intensive experiments as described below. First, 20 kg of Ni alloy was melted in a magnesia crucible in the laboratory. The melting equipment was a high-frequency induction furnace, and argon gas was blown from above the crucible to isolate it from the atmosphere. The raw materials used were pure Ni, electrolytic iron, ferrochrome, Mo, copper wire, Ti, nitrided ferrochrome, Co, W, NiNb, and B. Finally, Si and Al were added to deoxidize the alloy, and 1 kg of artificial slag of CaO-Al2O3-MgO-SiO2-F system was added, and the composition of the nonmetallic inclusions was carefully observed by sampling. In some experiments, deoxidization was performed only with Si without adding Al. Observation was performed using SEM. Analysis was performed using EDS. In particular, elemental mapping was performed carefully, and the structural morphology was carefully observed. It was found that at least 10 points of the inclusions need to be analyzed to find the compositional characteristics, 20 points is better, and 30 points or more is sufficient.

[0013] The alloy ingot cast into the mold was forged to a thickness of 20 mm, after which the surface was ground and cold rolled. The final plate thickness was 0.5 mm, and the surface was carefully observed to determine whether there were any defects.

[0014] As a result, it was found that the occurrence of defects is strongly related to the structural morphology of nonmetallic inclusions, and that a structural morphology in which CaO-Al2O3-MgO oxides contain MgO or MgO·Al2O3 has a high ability to suppress clustering. A schematic diagram of this is shown in Figure 1. Figure 1(a) shows a CaO-Al2O3-MgO oxide that completely contains MgO or MgO·Al2O3 within its approximately spherical surface, which is a good morphology that can suppress clustering. On the other hand, as shown in Figure 1(b), it was revealed that a morphology in which part of the outer edge is CaO-Al2O3-MgO, and most of the inside is high-melting point MgO or MgO·Al2O3 oxide that protrudes from the approximately spherical surface of the inclusion promotes clustering. Although the mechanism is largely unknown, it is assumed that the CaO-Al2O3-MgO melt acts as a sintering aid at steelmaking temperatures (1400-1550°C), adhering to each other and sintering. Based on experience, it has been assumed that the main sintering location is the inner wall of the submerged nozzle of the continuous casting machine.

[0015] On the other hand, it was also confirmed that sintering does not occur when MgO·Al2O3 or MgO is used alone. It became clear that the structure of the surrounding CaO-Al2O3-MgO oxide melt has a large effect on the final quality.

[0016] Furthermore, to evaluate the mechanical properties, test pieces were taken appropriately and the Vickers hardness was measured on a cross section parallel to the rolling direction, and it was found that in order to maintain a hardness of 90Hv or more and an elongation of 25% or more, it was necessary to contain appropriate amounts of Cr, Mo, Cu, Ti, and N. It was also found that it was more preferable to contain some Co, W, and Nb. Furthermore, it was found that the addition of B is desirable to maintain hot workability.

[0017] With this, for some steel types, the raw materials were melted in a 60-ton electric furnace, vacuum degassed in a VOD, and refined by adding quicklime from above and FeSi and / or Al at the same time to promote deoxidation and desulfurization. After that, slabs were produced in a continuous casting machine, and after surface grinding, they were hot rolled, cold rolled, and finally passed through an annealing and pickling line to produce 0.5 mm thick thin plates.

[0018] That is, the present invention was developed based on the above laboratory studies and through confirmation by actual equipment testing, as described below. The chemical compositions are all given in mass % and are as follows: C:0.001~0.03%, Si:0.01~0.5%, Mn:0.01~0.5%, P:0.01% or less, S:0.005% or less, Cr:0.5% or less, Mo:0 .1% or less, Cu: 0.1% or less, Al: 0.001~0.2%, Ti: 0.05% or less, Fe: 0.01~0.5%, Ca: 0.0001~0.02%, Mg: 0. It contains 0.0001-0.02%, N: 0.005% or less, O: 0.005% or less, one or more of Co, W, Nb, and B at 1% or less, with the balance being Ni and unavoidable impurities, and the average composition of non-metallic inclusions is MgO: 30-70%, Al2O3: 15-40%, SiO2: 30% or less, CaO: 10-40%, and MnO: 1% or less.

[0019] Furthermore, in a more preferred embodiment, the structural form of the nonmetallic inclusions is such that 70% or more of the nonmetallic inclusions in terms of number ratio to the total nonmetallic inclusions are any one or more of the following five types a to e. a: CaO-Al2O3-MgO oxide completely encloses MgO·Al2O3 within a roughly spherical surface b: CaO-Al2O3-MgO oxide c: CaO-Al2O3-MgO oxide completely encloses MgO within a roughly spherical surface d: MgO alone e: MgO·Al2O3 alone

[0020] In a more preferred embodiment, the CaO-Al2O3-MgO-based oxide described above is CaO: 20-60%, Al2O3: 30-60%, MgO: 1-30%, SiO2: 20% or less, and TiO2: 0.5% or less.

[0021] In the above-mentioned Ni alloy, it is desirable that MgO·Al2O3 or MnO is contained in an amount of 0.5% or less.

[0022] The above-mentioned simple MgO preferably contains Al2O3: 3% or less, SiO2: 1% or less, CaO: 10% or less, and MnO: 1% or less.

[0023] It is desirable that the above-described Ni alloy has a Vickers hardness of 90 Hv or more and an elongation of 25% or more.

[0024] The present invention also provides a manufacturing method, which involves melting raw materials in an electric furnace, then vacuum degassing in a VOD, adding quicklime, fluorite and magnesia source to form CaO-Al2O3-MgO-SiO2-F slag, and simultaneously adding ferrosilicon alloy and / or Al to deoxidize and desulfurize the slag, producing slabs in a continuous casting machine, grinding the surface, and then performing a hot rolling process and cold rolling. [Brief description of the drawings]

[0025]

Figure 1

Figure 2

[0026] The reasons for the numerical limitations of the present invention and the scientific viewpoints thereof will be explained below. The units below are % by mass. C: 0.001 to 0.03% C is an important element for maintaining the strength of Ni alloys. Therefore, 0.001% is necessary. On the other hand, if it is added in excess of 0.03%, it has the drawback of forming carbides of Ti and the like, which leads to embrittlement. Therefore, the addition of 0.001-0.03% is controlled by adding a carbon source after desulfurization in VOD. It is preferably 0.002-0.025%, and more preferably 0.005-0.022%.

[0027] Silicon: 0.01 to 0.5% Silicon is an effective element for deoxidation and is very important in the present invention. Deoxidation can be carried out according to the following formula. In other words, deoxidation is carried out by adding FeSi alloy or pure Si during VOD. Si +2 O =(SiO2) …(1) Here, the underlined parts indicate the components in the molten steel, and the parentheses indicate the components in the slag. As will be described later, by lowering the activity coefficient of SiO2 in the slag, deoxidation can be effectively promoted and the oxygen concentration can be controlled to the oxygen concentration of the present invention. Furthermore, desulfurization can be achieved at the same time. 0.01% is necessary to achieve this effect, and if it exceeds 0.5%, not only will the corrosion resistance decrease, but the steel will become embrittled. Therefore, the range is specified as 0.01 to 0.5%. The range is preferably 0.03 to 0.3%, and more preferably 0.05 to 0.28%.

[0028] Mn: 0.01 to 0.5% Mn is an element useful for deoxidization and is therefore an extremely effective element, and therefore the content is specified to be 0.01 to 0.5%, preferably 0.03 to 0.47%, and more preferably 0.03 to 0.4%.

[0029] P:0.01% or less P is a harmful element that not only segregates to grain boundaries and reduces corrosion resistance, but also causes red brittleness during welding, leading to cracking. P can be removed as P2O5 in the slag by performing oxygen blowing in an electric furnace. Therefore, the content is set to 0.01% or less. It is preferably 0.008% or less, and more preferably 0.002% or less.

[0030] S: 0.005% or less S is a harmful element because it segregates at grain boundaries and forms MnS, which becomes the starting point of pitting corrosion. It also reduces hot workability and causes edge cracks. Therefore, the content is set at 0.005% or less. As will be described in detail later, desulfurization can be promoted by the following reaction formula. 3(CaO)+2Al+3S=(Al2O3)+3(CaS) …(2) 2(CaO)+Si+2S=(SiO2)+2(CaS)…(3) The desulfurization reaction can be promoted efficiently by reducing the activity coefficient of alumina and silica in the slag. If the content is 0.005% or less, the above problems can be avoided, so this range is specified. The content is preferably 0.003% or less, more preferably 0.0015% or less, and even more preferably 0.0008% or less.

[0031] Ni:99% or more Ni is a major element in the present invention and is an important element for maintaining mechanical properties, corrosion resistance, and workability. In the present invention, it is treated as the balance. If it is less than 99%, the required corrosion resistance will be exceeded and the mechanical properties will not be satisfied. The properties required for electronic parts, such as electrical conductivity, will also be impaired. Therefore, it is specified to be 99% or more. It is preferably 99.2% or more, more preferably 99.3% or more, and even more preferably 99.4% or more.

[0032] Cr:0.5% or less In the present invention, Cr is an important element for maintaining strength through solid solution strengthening. However, if the Cr content is too high, there is a risk of forming MnO-Cr2O3-based inclusions. Therefore, the Cr content is specified to be 0.5% or less. It is preferably 0.4% or less, and more preferably 0.3% or less. Although not limited, a content of 0.01% or more is desirable.

[0033] Mo: 0.1% or less Mo, like Cr, is an important element for maintaining strength through solid solution strengthening. However, if the content is too high, it will cause abnormal oxidation during heating in the manufacturing process. Therefore, the content is set at 0.1% or less. The content is preferably 0.08% or less. Although not limited, a content of 0.01% or more is desirable.

[0034] Cu: 0.1% or less Like Cr, Cu is an important element for maintaining strength through solid solution strengthening. However, if the Cu content is too high, it can cause the Ni alloy plate to soften. Therefore, the Cu content is set to 0.1% or less. The Cu content is preferably 0.05% or less, and more preferably 0.03% or less.

[0035] Al: 0.001 to 0.2% Al is a useful element for deoxidation. It also improves high-temperature oxidation resistance. On the other hand, if the content is too high, AlN is formed, impairing hot workability, and the Ca and Mg concentrations become too high, exceeding the upper limit of the range of the present invention. As a result, harmful CaO-based inclusions are formed, and a low-melting point compound called NiMg2 is formed, reducing hot workability. The deoxidation reaction proceeds as follows. 2 Al +3 O =(Al2O3) … (4) As will be described in detail later, by lowering the alumina activity in the slag, deoxidation proceeds efficiently. Furthermore, desulfurization also becomes possible at the same time. Therefore, the content is specified to be 0.001 to 0.2%. It is preferably 0.002 to 0.18%, more preferably 0.005 to 0.15%, and further preferably 0.008 to 0.13%.

[0036] Ti: 0.05% or less Ti fixes N to form TiN, which prevents the formation of blowholes due to the nitrogen exceeding its solubility during solidification. Therefore, the content is specified to be 0.05% or less. It is preferably 0.02% or less. It is more preferably 0.01% or less.

[0037] Fe: 0.01 to 0.5% In the present invention, Fe is an important element for maintaining strength through solid solution strengthening. However, if the content is too high, the purity of the Ni alloy decreases and the corrosion resistance is impaired. Therefore, the content is specified to be 0.01 to 0.5%. The content is preferably 0.03 to 0.4%, and more preferably 0.04 to 0.3%.

[0038] Ca: 0.0001-0.02% Ca is an important element for controlling the structure of nonmetallic inclusions to the preferred CaO-Al2O3-MgO oxides. By controlling the structure in this way, it is possible to manufacture sound products without clustering or forming surface defects. Ca is effectively added by utilizing the following reaction: 3(CaO)+2 Al =(Al2O3)+3 Ca …(5) 2(CaO)+ Si =(SiO2)+2 Ca …(6) To control this reaction, the activity of alumina and silica in the slag should be controlled within an appropriate range. This will be explained in detail in the manufacturing method. On the other hand, if the activity is too high, harmful CaO inclusions are formed, which promotes clustering and creates defects. Therefore, the content is specified to be 0.0001 to 0.02%. The content is preferably 0.0005 to 0.015%, and more preferably 0.001 to 0.01%.

[0039] Mg: 0.0001-0.02% Mg is an important element for controlling the structure of nonmetallic inclusions to the preferred CaO-Al2O3-MgO oxide, MgO, and MgO·Al2O3. By controlling the structure in this way, it is possible to manufacture sound products without clustering or forming surface defects. Mg is effectively added by utilizing the following reaction: 3(MgO)+2 Al =(Al2O3)+3 Mg …(7) 2(MgO)+ Si =(SiO2)+2 Mg …(8) To control this reaction, the activity of alumina and silica in the slag should be controlled within an appropriate range. This will be explained in detail in the manufacturing method. On the other hand, if it is too high, Mg vaporizes during solidification and forms blowholes, which causes surface defects. Therefore, the content is specified to be 0.0001 to 0.02%. It is preferably 0.0005 to 0.015%, and more preferably 0.001 to 0.01%.

[0040] N: 0.005% or less N is an important element for maintaining strength through solid solution strengthening. However, if the content is too high, TiN clusters are formed, causing surface defects. Therefore, the content is specified to be 0.005% or less. It is preferably 0.003% or less, and more preferably 0.002% or less.

[0041] O: 0.005% or less The oxygen content must be reduced because it increases the number of nonmetallic inclusions and forms surface defects. Therefore, the oxygen content is set to 0.005% or less. It is preferably 0.003% or less, more preferably 0.001% or less, and even more preferably 0.0008% or less.

[0042] One or more of Co, W, Nb, and B should be less than 1% Co is an effective element because it behaves in the same way as Ni. It is also sometimes included in pure Ni raw materials, and plays an important role in terms of utilizing inexpensive raw materials. W is a beneficial element because it maintains mechanical properties. Nb is useful for maintaining strength through solid solution strengthening. B improves hot workability. It is more preferable to contain one or more of these elements at 1% or less. In other words, they may be added as necessary.

[0043] The balance of the Ni alloy of the present invention is Ni. In addition, it may contain trace amounts of unavoidable impurities such as Pb, Sn, Ta, Ag, Na, K, and Zr. All of these are mixed in from the raw materials, pure Ni and ferroalloys.

[0044] Next, the average composition of the nonmetallic inclusions will be described. The average composition of the nonmetallic inclusions is as follows: MgO: 30~70% MgO is effective for forming harmless CaO-Al2O3-MgO oxides, and is also extremely effective for forming simple MgO and simple MgO·Al2O3, which are similarly harmless. Therefore, the content is specified to be 30 to 70%. The preferred content is 35 to 65%.

[0045] Al2O3: 15-40% Al2O3 is effective for forming harmless CaO-Al2O3-MgO oxides, and is also extremely effective for forming MgO·Al2O3, which is also harmless. However, if it is higher than 40%, it forms harmful Al2O3 simple substance, which causes defects. Therefore, it is specified to be 15-40%. It is preferably 18-39%.

[0046] SiO2: 30% or less SiO2 is a compound present in CaO-Al2O3-MgO oxides, and is effective in lowering the melting point. However, if it exceeds 30%, it acts in the direction of increasing the oxygen concentration, which not only increases the number of nonmetallic inclusions but also forms harmful MnO-Cr2O3 oxides, resulting in defects. Therefore, it is specified to be 30% or less. Preferably, it is 28% or less.

[0047] CaO: 10-40% CaO is effective for forming harmless CaO-Al2O3-MgO oxides, but if the content is too high, harmful CaO inclusions are formed, resulting in defects. Therefore, the content is specified to be 10 to 40%. The content is preferably 12 to 39%. The content is more preferably 13 to 38%.

[0048] MnO: 1% or less MnO is harmless because it dissolves in the MgO sites of MgO and MgO·Al2O3 inclusions. However, if the content is too high, it forms harmful MnO-Cr2O3 oxides, which can cause defects. Therefore, the content is set at 1% or less. It is preferably 0.9% or less. It is more preferably 0.8% or less.

[0049] Cr2O3: 1.5% or less Although not particularly limited, a high Cr2O3 content makes it easier for MnO-Cr2O3-based inclusions to form. Furthermore, the oxygen concentration in the molten steel also increases, increasing the number of nonmetallic inclusions and causing defects. Therefore, it is preferable that the Cr2O3 content is 1.5% or less. More preferably, it is 1.3% or less. Even more preferably, it is 0.6% or less.

[0050] There are several methods for determining the average composition. It can be clarified by randomly analyzing 10 points using SEM / EDS. In this case, it is necessary to analyze two points on the periphery of the center, and the average can be obtained by taking a mapping and measuring the area ratio by image analysis. It is preferable to analyze 20 points or more, and more preferably 30 points or more. The other is the so-called electrolytic method, which is widely known as the Speed ​​method. In other words, the metal part is dissolved by applying an appropriate potential in an appropriate solution. After that, the non-metallic inclusions that become the residue are collected by filtration. The average composition can be obtained all at once by subjecting this to chemical analysis. There is no limitation on the analysis method.

[0051] Furthermore, the structural morphology of nonmetallic inclusions will be explained. In a more preferred embodiment, nonmetallic inclusions that account for 70% or more of the total number of nonmetallic inclusions are one or more of the following five types a to e. The structural morphologies corresponding to a to e are also shown in Figures 2(a) to (e). a: CaO-Al2O3-MgO oxide completely encloses MgO·Al2O3 within a roughly spherical surface b: CaO-Al2O3-MgO oxide c: CaO-Al2O3-MgO oxide completely encloses MgO within a roughly spherical surface d: MgO alone e: MgO·Al2O3 alone Here, being completely contained within an approximately spherical surface means that the internal material is completely contained within the material on the outer edge as shown in FIG. 1(a), and does not include a state in which the internal material partially protrudes to the outside as shown in FIG. 1(b).

[0052] As explained in the means for solving the problems, the form in FIG. 1(b) does not appear in the following operation. To control these structural forms, it is sufficient to control the chemical components Si, Al, Ca, Mg, O, and Mn within the range of the present invention, but this is not all. a and c are also characteristic of the present application. To achieve these structural forms, the vacuum mixing process in the VOD is the key. Dolomite is preferable for the bricks in the VOD. In the deoxidation period, quicklime is first charged, and at the same time, fluorite and waste bricks containing MgO are charged. MgO waste bricks can be charged as needed. After that, when ferrosilicon alloy or pure Si and Al are charged, Si and Al are added to the molten slag that has already been formed. Deoxidation is possible with only Si. This directly reacts with CaO and MgO in the slag, effectively adding Ca and Mg.

[0053] Mg is supplied to the molten steel in advance according to the reactions of equations (7) and (8). The reason for this is unclear, but the reaction of Ca is delayed. This dissolved Mg reacts first with the original non-metallic inclusions, silica and alumina, as shown below. 2 Mg +SiO2(inclusion)=2MgO(inclusion)+2 Si …(9) 3 Mg +Al2O3(inclusion) = 3MgO(inclusion) + 2 Al …(10) 2 Mg +4 Al + 4SiO2(inclusions) = 2MgO·Al2O3(inclusions) + 4 Si …(11) 3 Mg + 4Al2O3(inclusions) = MgO·Al2O3(inclusions) + 2 Al …(12) As shown in formulas (9) to (12) above, simple MgO and simple MgO·Al2O3 are formed initially. After that, Ca is supplied from the slag, and the Ca in the molten steel reacts with the inclusions mentioned above, resulting in the vigorous formation of CaO-Al2O3-MgO oxides on the surface. These molten oxides then cover the simple MgO and simple MgO·Al2O3, rendering them harmless. In other words, they are molten and behave as harmless CaO-Al2O3-MgO inclusions. Therefore, if the non-metallic inclusions are spherical, they will behave as described above and will be harmless.

[0054] Furthermore, the composition range of the above CaO-Al2O3-MgO oxide will be explained. CaO: 20~60%, Al2O3: 30~60%, MgO: 1~30%, SiO2: 20% or less, TiO2: 0.5% or less The above range was set because the molten state can be maintained at the steelmaking temperature, i.e., near 1500°C. In particular, if the CaO content is too high, harmful CaO simple inclusions are formed, so CaO: 20-60% was specified. If the Al2O3 content is too high, simple Al2O3 is formed, so Al2O3: 30-60% was specified. If the SiO2 content is too high, harmful MnO-Cr2O3 inclusions are formed, so it was set to 20% or less.

[0055] MnO concentration in MgO·Al2O3: 0.5% or less Since MnO dissolves in the MgO sites of MgO·Al2O3, it is possible to render MnO harmless. Therefore, the content is set at 0.5% or less.

[0056] MgO simple inclusions contain Al2O3: 3% or less, SiO2: 1% or less, CaO: 10% or less, MnO: 1% or less Since MgO inclusions are harmless, it is desirable for them to dissolve in the inclusions to some extent. Taking into account the solubility limit, the contents are set at Al2O3: 3% or less, SiO2: 1% or less, CaO: 10% or less, and MnO: 1% or less.

[0057] The present invention also provides a manufacturing method. That is, the raw materials are melted in an electric furnace, and then vacuum degassed in a VOD. The raw materials may be blended according to the desired components, such as pure Ni, ferrosilicon alloy, ferrochrome alloy, iron scrap, Mo, Mo trioxide, ferromolybdenum alloy, ferroniobium alloy, and copper wire.

[0058] After the decarburization and dephosphorization processes in the electric furnace are completed, the slag is first removed. Then, either or both of ferrosilicon alloy and Al are added to form CaO-Al2O3-MgO-SiO2-F slag, which is then deoxidized and desulfurized. A slab is then produced in a continuous casting machine, the surface is ground, and the slab is then subjected to a hot rolling process and cold rolling. At this time, in order to control the structure of the nonmetallic inclusions to a desirable form, it is necessary to control the slag composition within an appropriate range.

[0059] The following range is desirable for CaO-Al2O3-MgO-SiO2-F slag. CaO: 35-70% The CaO concentration can be adjusted by adding quicklime. CaO has a tremendous effect on deoxidation and desulfurization. In other words, as shown in formulas (2) and (3), desulfurization is possible by making CaO exist stably as CaS in the slag. However, if the CaO concentration is higher than 70%, CaO inclusions are formed. Therefore, 35 to 70% is preferable. Preferably, it is 40 to 65%. More preferably, it is 50 to 63%.

[0060] Al2O3: 35% or less Al2O3 is effective in making CaO-Al2O3-MgO-SiO2-F slag molten. On the other hand, if it exceeds 35%, it creates Al2O3 simple inclusions and promotes clustering. Therefore, it is desirable to keep it at 35% or less. Preferably, it is 30% or less. More preferably, it is 25% or less.

[0061] MgO: 3~25% MgO is effective in making CaO-Al2O3-MgO-SiO2-F slag molten. On the other hand, if the MgO concentration is high, the Mg concentration in the molten steel will be high, and Mg gas will be released during solidification, forming blowholes. Therefore, 3 to 25% is preferable. 5 to 20% is more preferable, and 7 to 15% is even more preferable.

[0062] SiO2: 32% or less SiO2 is effective in molten CaO-Al2O3-MgO-SiO2-F slag. On the other hand, if the SiO2 concentration is high, the oxygen concentration in the molten steel will be high and the nonmetallic inclusion composition will also be MnO-Cr2O3. As a result, surface defects will occur. Therefore, it is preferable that the SiO2 content is 32% or less. More preferably, it is 30% or less. Even more preferably, it is 25% or less.

[0063] F: 1-10% F is added as fluorite. F is effective in molten CaO-Al2O3-MgO-SiO2-F slag. On the other hand, if the F concentration is high, it will corrode the bricks of the VOD and the ladle, shortening their lifespan. Therefore, 1 to 10% is preferable. 2 to 9% is more preferable.

[0064] Furthermore, it is desirable that the Cr2O3 and FeO concentrations are low. Cr2O3: 1% or less If the Cr2O3 concentration is high, the oxygen concentration will increase and cause the formation of MnO-Cr2O3-based inclusions. Therefore, it is best to keep it at 1% or less. It is preferably 0.7% or less. It is more preferably 0.6% or less.

[0065] FeO: 1% or less If the FeO concentration is high, the oxygen concentration will increase and cause the formation of MnO-Cr2O3-based inclusions. Therefore, it is preferable that the FeO concentration is 1% or less. It is preferably 0.9% or less. It is more preferably 0.8% or less.

[0066] Furthermore, a high S concentration is desirable because it indicates that desulfurization has progressed normally. A concentration of 0.01% or more is desirable, and a concentration of 0.02% or more is even more desirable.

[0067] In the present invention, it is also necessary to adjust the mechanical properties. That is, the Vickers hardness is specified to be 90Hv or more, and preferably 250Hv or less. The elongation must be 25% or more, and preferably 35% or more. EXAMPLES

[0068] The effectiveness of the present invention will be clarified by showing examples below. The raw materials were melted in an electric furnace of 60 to 70 tons, and then decarburized and refined in a VOD. The raw materials consisted of mainly pure Ni, stainless steel scrap, ferrosilicon alloy, ferrosilicon alloy, iron scrap, Mo, Mo trioxide, ferromolybdenum alloy, ferroniobium alloy, ferrochrome alloy, copper wire, etc., which were blended according to the target steel type.

[0069] After the decarburization and dephosphorization processes in the electric furnace were completed, the slag was removed in a slag pot. Then, gas components were removed by vacuum degassing in the VOD. Then, quicklime and waste bricks containing magnesia, and fluorite were added, followed by pure Si or ferrosilicon alloy. Finally, Al was added to form a CaO-Al2O3-MgO-SiO2-F slag. Even when Al was not added, the Al impurity in the FeSi alloy was oxidized to supply alumina.

[0070] In some Ni alloys, Nb, Mo, C, Co, Cr, B, Ni, and other alloying elements were added to precisely adjust the chemical composition. After deoxidization and desulfurization, slabs of 200 mmt x 1200 mmw x 7 m length were produced using a continuous casting machine, and the oscillation marks on the surface were ground. After heating to 1000 to 1250 °C depending on the steel type, the slabs were subjected to a hot rolling process, and finally cold rolling was performed and passed through an annealing and pickling line. In this way, 1 mm cold rolled coils were produced for all steel types.

[0071] At this time, the evaluation was carried out by the following methods. 1) Chemical composition: The surface of a 30mm diameter x 10mm height suction sample taken from the tundish of a continuous casting machine was ground with a grinder. Major elements were analyzed by fluorescent X-ray analysis. Some C and S were analyzed by the combustion method. N and O were also analyzed by the infrared absorption method. 2) Slag components: Slag was collected with an iron bar and crushed. This was then pressed into a cylindrical sample. The values ​​of this sample were determined using X-ray fluorescence analysis. F was determined by chemical analysis. 3) Average composition of non-metallic inclusions: The above-mentioned suction sample was cut out, embedded in resin and mirror-polished. This was then placed in a SEM for observation and quantitative analysis. Thirty inclusions with a size of 5μm or more were randomly selected and the center and periphery were analyzed. The element distribution of each inclusion was determined by mapping, and the ratio of each phase was calculated by image analysis. Taking into account the weighted average, a representative analysis value for each inclusion particle was obtained. This was determined by calculating the average value of the 30 points. 4) Morphology of nonmetallic inclusions: The morphology was classified when observed and analyzed as described above. The morphology shown in Figure 1(b) was not confirmed. 5) Composition of each oxide: Calculated from the composition of each oxide phase described above. 6) Mechanical properties: Vickers hardness was measured with a micro Vickers hardness tester after embedding and polishing a cross section parallel to the rolling direction. A Vickers hardness of 90Hv or more was deemed a pass and marked with a "good" mark, and anything less than that was deemed a fail and marked with a "bad" mark. Tensile test pieces were taken and elongation was measured with an extensometer. An elongation of 25% or more was deemed a pass and marked with a "good" mark, and anything less than that was deemed a fail and marked with a "bad" mark. 7) Overall evaluation: An inspector visually evaluated a 1 mm thick Ni alloy plate when it was threaded. The evaluation results were determined as follows. The allowable range for not cutting the plate is within 10 mm of the plate surface. 2 This means that there are up to three linear scratches of 1mm or more in length per unit area. Passed: No surface defects (100% non-defective product at time of shipment) Passed: Some surface defects occurred but within the required quality tolerance (95% pass rate). Pass: △ Surface defects occurred in some areas, but the product can be shipped after partial cutting (80% pass rate) Rejected: × Surface defects occurred along the entire length of the coil, and the coil was scrapped (0% defective product rate). Additionally, mechanical properties were considered, but evaluation of surface defects was prioritized.

[0072] [Table 1]

[0073] [Table 2]

[0074] The structural morphologies of the examples are shown in Figures 2(a) to (e), and those of the comparative examples are shown in Figures 2(f) to (h). The reason why the chemical components do not add up to 100% is due to unavoidable impurities. For invention examples Nos. 1 to 14, the chemical analysis was within the range, and the slag composition also satisfied the desired range. As a result, the structural morphology of the non-metallic inclusions also satisfied the ranges a to e. Ultimately, all products were judged to be acceptable.

[0075] However, in No.5, one alumina inclusion and one MnO-Cr2O3 inclusion were confirmed. In No.8, one CaO inclusion was observed. Therefore, the evaluation was rated as good. In No.10, one Al2O3 inclusion and one MnO-Cr2O3 inclusion were observed. Therefore, the evaluation was rated as good. Furthermore, in No.11, the MnO concentration in the MgO·Al2O3 was high, and the SiO2 and MnO in the MgO inclusions were high, while CaO inclusions, Al2O3 inclusions, and MnO-Cr2O3 inclusions were confirmed. As a result, the evaluation was rated as fair.

[0076] Next, a comparative example will be described. No.15 had low Si. Conversely, Al was high and the CaO concentration in the slag exceeded the desired range, resulting in high Ca and Mg concentrations. As a result, MgO and CaO were not included in the average composition of the inclusions. The structure also had more f·CaO alone, with the CaO in the CaO-Al2O3-MgO oxides being high. In other words, the CaO alone inclusions became the center, causing defects and resulting in scrapping.

[0077] In No. 16, the Si concentration was too high, which resulted in high Ca and Mg concentrations. The high Si concentration also led to a high SiO2 concentration in the slag. The F concentration was also low, resulting in a lack of slag fluidity. The Ti and N concentrations were both too high, and TiN clusters were formed. In terms of the average composition of the inclusions, MgO and CaO were out of range, and the alumina, MgO, and SiO2 in the CaO-Al2O3-MgO oxide system were out of range, and the structural morphology also showed the formation of many f·CaO simple inclusions. The formation of many TiN and CaO simple inclusions caused numerous surface defects, resulting in the coil becoming scrap.

[0078] In No.17, the Si content was low, Mn yield was low, and Al was not added, resulting in low Ca and Mg concentrations. In addition, the oxygen concentration was high, and the number of non-metallic inclusions increased. In addition, the slag composition was high in silica and low in CaO, which was outside the range, and this had a negative effect on the inclusion composition. The average composition of the inclusions was outside the range for all oxides, and the microstructure also showed many h·MnO-Cr2O3-based inclusions. Alumina and silica were also not included in the CaO-Al2O3-MgO-based oxide, and MnO-Cr2O3-based inclusions were confirmed. As a result, surface defects occurred along the entire length, and the coil was eventually scrapped.

[0079] No.18 had a high Al concentration, resulting in a high alumina concentration in the slag, while the CaO concentration was low. The average composition of the nonmetallic inclusions was 100% alumina, and the microstructure consisted of only g·Al2O3 inclusions. The content of elements that maintain strength, such as Cr, was low, and both the hardness and elongation were outside the range. As a result, surface defects occurred along the entire length, causing the material to become scrap.

[0080] No.19 had a low Al concentration, which resulted in low Ca and Mg concentrations and a high oxygen concentration. The average composition of nonmetallic inclusions was high in Cr2O3, and three types of structure were formed: f, g, and h. In particular, many h·MnO-Cr2O3 inclusions were observed. Furthermore, MgO·Al2O3 simple inclusions and components dissolved in MgO simple inclusions were also outside the range. In addition, the Ti and N concentrations were high, and TiN clusters were observed. Furthermore, the elements that maintain strength, such as Cr, were low, and both the hardness and elongation were outside the range. As a result, surface defects occurred along the entire length, resulting in scrapping.

[0081] No. 20 had high Ti and N values, which caused severe TiN clusters to form surface defects. In Table 2, all of the inclusion morphologies are a and b, which may seem good at first glance, but this is because TiN is not counted as an inclusion. Furthermore, the values ​​of elements that maintain strength, such as C and Cr, were low, and both hardness and elongation were outside the range. As a result, the product could not be shipped and was scrapped.

Claims

1. The steel sheet contains, in mass %, C: 0.001-0.03%, Si: 0.01-0.5%, Mn: 0.01-0.5%, P: 0.01% or less, S: 0.005% or less, Cr: 0.5% or less, Mo: 0.1% or less, Cu: 0.1% or less, Al: 0.001-0.2%, Ti: 0.05% or less, Fe: 0.01-0.5%, Ca: 0.0001-0.02%, Mg: 0.0001-0.02%, N: 0.005% or less, O: 0.005% or less, and one or more of Co, W, Nb, and B are 1% or less, with the balance being Ni and unavoidable impurities. The average composition of the non-metallic inclusions is MgO: 30-70%, Al: 0.001-0.2%, Ti: 0.05% or less, Fe: 0.01-0.5%, Ca: 0.0001-0.02%, Mg: 0.0001-0.02%, N: 0.005% or less, O: 0.005% or less, and 1% or less of one or more of Co, W, Nb, and B. 2 O 3 :15~40%, SiO 2 : 30% or less, CaO: 10 to 40%, MnO: 1% or less, and having excellent surface properties and mechanical properties.

2. The Ni alloy having excellent surface properties and mechanical properties as described in claim 1, characterized in that the structural form of the non-metallic inclusions is such that 70% or more of the non-metallic inclusions in terms of number ratio to the total non-metallic inclusions are any one or more of the following five types a to e. a: CaO-Al 2 O 3 -MgO-based oxide is MgO.Al within the approximately spherical surface 2 O 3 A form that completely encompasses b: CaO-Al 2 O 3 -MgO acid compound c: CaO-Al 2 O 3 - A form in which MgO-based oxide completely encapsulates MgO within a substantially spherical surface d: MgO alone e: MgO.Al 2 O 3 Single

3. The CaO—Al 2 O 3 -MgO-based oxides are CaO: 20-60%, Al 2 O 3 :30~60%, MgO:1~30%, SiO 2 3. The Ni alloy having excellent surface properties and mechanical properties according to claim 2, characterized in that: Mn: 20% or less, TiO2: 0.5% or less.

4. The MgO.Al 2 O 3 3. The Ni alloy having excellent surface properties and mechanical properties according to claim 2, characterized in that it contains 0.5% or less of MnO.

5. The MgO simple substance is Al 2 O 3 : 3% or less, SiO 2 3. The Ni alloy having excellent surface properties and mechanical properties according to claim 2, characterized in that it contains: 1% or less of Mo, 10% or less of CaO, and 1% or less of MnO.

6. 2. The Ni alloy according to claim 1, characterized in that it has a Vickers hardness of 90 Hv or more and an elongation of 25% or more.

7. The method for producing the Ni alloy according to any one of claims 1 to 6, wherein the method comprises melting raw materials such as pure Ni in an electric furnace, then subjecting the raw materials to vacuum degassing in a VOD, and then adding quicklime, fluorite and a magnesia source to produce a CaO-Al alloy. 2 O 3 -MgO-SiO 2 A method for producing a Ni alloy having excellent surface properties and mechanical properties, characterized in that a -F-based slag is formed and at the same time a ferrosilicon alloy and / or Al is added to perform deoxidation and desulfurization, then a slab is produced using a continuous casting machine, the surface is ground, and then a hot rolling process is performed, followed by cold rolling.

Citation Information

Patent Citations

  • Production of hot coil for pure nickel

    JP1988168259A

  • Nickel for electrical equipment, excellent in hot workability

    JP1996143996A

  • Nickel material

    JP2003089835A

  • Method for producing pure nickel rolling stock

    JP2005082886A

  • Pure nickel sheet and method for producing pure nickel sheet

    JP2010090438A